Cardiac Fibrosis: The Fibroblast Awakens. Issue 6 (18th March 2016) - Travers, Joshua G.; Kamal, Fadia A.; Robbins, Jeffrey; Yutzey, Katherine E.; Blaxall, Burns C.
Abstract : Myocardial fibrosis is a significant global health problem associated with nearly all forms of heart disease. Cardiac fibroblasts comprise an essential cell type in the heart that is responsible for the homeostasis of the extracellular matrix; however, upon injury, these cells transform to a myofibroblast phenotype and contribute to cardiac fibrosis. This remodeling involves pathological changes that include chamber dilation, cardiomyocyte hypertrophy and apoptosis, and ultimately leads to the progression to heart failure. Despite the critical importance of fibrosis in cardiovascular disease, our limited understanding of the cardiac fibroblast impedes the development of potential therapies that effectively target this cell type and its pathological contribution to disease progression. This review summarizes current knowledge regarding the origins and roles of fibroblasts, mediators and signaling pathways known to influence fibroblast function after myocardial injury, as well as novel therapeutic strategies under investigation to attenuate cardiac fibrosis.